Antidiabetic, Antioxidant and Anti-Inflammatory Activities of Residual Aqueous Fraction of Ethulia conyzoides in Induced Type 2 Diabetic Rats - Helen Omasan Okotie; Tayo Micheal Anjuwon; Okwubenata Lilian Okonkwo; Danladi Amodu Ameh; Dorcas Bolanle James (Tropical Life Sciences Research, 2023)
Oxidative stress and inflammation have been proven to be implicated in the pathogenesis of type 2 diabetes. Recent studies showed that Ethulia conyzoides had in-vitro antioxidant activity. This study investigated the in-vivo antidiabetic, antioxidant, and anti-inflammatory potential of the residual aqueous fraction of Ethulia conyzoides in type 2 diabetic-induced male Wistar rats. Sub-acute antidiabetic studies were done with varying doses (100, 200, and 400 mg/kg body weight) of residual aqueous fraction for 21 days. Blood glucose levels, serum insulin, and in vivo antioxidant and pro-inflammatory cytokines— tumour necrosis factor- ? (TNF-?) and interleukin-1? (IL-1?) —were measured at the end of the treatment. When rats were given different concentrations of residual aqueous fraction, there was a significant (p < 0.05) reduction in blood glucose, malondialdehyde (MDA), IL-1?, and TNF-? levels, as well as a significant (p < 0.05) increase in SOD (superoxide dismutase), catalase and insulin levels when compared to the diabetic control group. Furthermore, the 400 mg/kg body weight dosage concentration was found to be the most effective. This result suggests that the residual aqueous fraction of Ethulia conyzoides possesses significant antidiabetic, antioxidant and anti-inflammatory activities.